Хімічна модифікація відомого протитуберкульозного препарату - Галатенко, Н.А.; Рожнова, Р.А.; Замуліна, Л.І.; Гладир, І.І. (Видавничий дім "Академперіодика" НАН України, 2008)
A new hydrazone on the basis of lactose and isonicotinic acid hydrazide is synthesized. The
structure of chemically modificated medicinal preparation is studied by comparison of the
NMR-spectra of the initial compounds and the end product.